2018
DOI: 10.5005/jp-journals-10019-1219
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Mechanical Properties of Cention N with Conventionally used Restorative Materials—An In Vitro Study

Abstract: Objective: This study compared the compressive strength and flexural strength of Centurion N with other conventionally used restorative materials.Materials and methods: Cention N, Amalgam, Glass Ionomer Cement and Hybrid composite resin was used for sample fabrication. A total of 80 specimens were prepared. Forty samples (n = 10 each) were prepared for compressive strength and other 40 samples (n = 10 each) were prepared for flexural strength using aluminum split molds.The samples were tested using a universal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
1
8
0
2
Order By: Relevance
“…This study corroborates to Mishra et al 17 which showed that Cention N flexural strength did not differ from the studied resins. A good explanation for Cention N behavior may lie in the fact that it does not have Bis-GMA (bisphenol A-glycidyl methacrylate), HEMA (2-hydroxyethyl methacrylate), or TEGDMA (triethylene glycol dimethacrylate), being UDMA (urethane-dimethacrylate) its main monomeric matrix component 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study corroborates to Mishra et al 17 which showed that Cention N flexural strength did not differ from the studied resins. A good explanation for Cention N behavior may lie in the fact that it does not have Bis-GMA (bisphenol A-glycidyl methacrylate), HEMA (2-hydroxyethyl methacrylate), or TEGDMA (triethylene glycol dimethacrylate), being UDMA (urethane-dimethacrylate) its main monomeric matrix component 15 .…”
Section: Discussionsupporting
confidence: 92%
“…Equia Forte showed lower flexural strength values but like RIVA. Mishra et al 17 . found that Cention N and Equia Forte showed flexural strength reduction over time with lower values than Vitremer.…”
Section: Discussionmentioning
confidence: 99%
“…The highest µSBS values of Cention N can be explained by a possible chemical bonding that may have occurred between MTA and alkasite, which is able to release calcium and hydroxide ions. 13 Although Cention N might be used with or without adhesive, 37 it was used with an adhesive to achieve a standardization among the samples in this study. This may also explain the high µSBS values in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Three esthetic restorative materials, a bulkfill resin composite, a universal nanohybrid Ormocer and a CAD -CAM resin nanoceramic were used in this study. Materials, composition and manufacturers are listed in Table (1)…”
Section: Methodsmentioning
confidence: 99%
“…regarding restorative materials technologies over decades of time (1)(2)(3)(4)(5) . Also, dental restorative materials should provide adequate years of clinical service without prominent deterioration in mechanical and physical properties.…”
Section: Assessment Of Surface Roughness Of a Cad -Cam Resin Nano-cer...mentioning
confidence: 99%